Letter - Halifax, Edward Frederick Lindley Wood, Earl of, 1881-1959
012a-0091-001 Foreign Office, S.W.1 2nd May, 1938. Dear Sir Walter, In continuation of my letter of the 7th April about Señor Bratos, the Spanish Trades Union leader who is believed to be imprisoned at Bilbao, I write to say that we have passed on the information which you sent me to our Agent at Burgos for such action as he may be able to take on this prisoner's behalf. I shall not fail to keep you informed of any further developments. sincerely, Halifax Sir Walter Citrine, K.B.E. 292/946/12a/91